The telomere effect : a revolutionary approach to living younger, healthier, longer - Blackburn, Elizabeth H. (Elizabeth Helen), 1948-; Epel, Elissa (New York, NY : Grand Central Publishing, Hachette Book Group, 2017)
"Have you wondered why some 60-year olds look and feel like 40-year-olds and why some 40-year-olds look and feel like 60-year-olds? While many factors contribute to aging and illness, Nobel Prize-winning Doctor Elizabeth Blackburn discovered biological markers, called telomerase, the enzyme that replenishes telomeres, which protect our DNA Dr. Blackburn discovered that the length and health of one's telomeres provides a biological basis for the long hypothesized mind-body connection. But perhaps more importantly, along with leading health Psychologist, Dr. Elissa Epel, discovered that there are things we can do to improve and lengthen our telomeres to keep us vital and disease-free, "--NoveList
Telomeres : a pathway to living younger -- How prematurely aging cells make you look, feel, and act old -- The power of long telomeres -- Telomerase, the enzyme that replenishes telomeres -- Your cells are listening to your thoughts -- Unraveling : how stress gets into your cells -- Mind your telomeres : negative thinking, resilient thinking -- When blue turns to gray : depression and anxiety -- Help your body protect its cells -- Training your telomeres : how much exercise is enough? -- Tired telomeres : from exhaustion to restoration -- Telomeres weigh in : a healthy metabolism -- Food and telomeres : eating for optimal cell health -- Outside in: the social world shapes your telomeres -- The places and faces that support our telomeres -- Pregnancy : cellular aging begins in the womb -- Childhood matters for life : how the early years shape telomeres
Includes bibliographical references and index
Keywords: Aging -- Genetics; Telomere -- Physiology; Longevity; Longevity -- Genetic aspects; HEALTH & FITNESS -- Healthy Living; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Longevity; Longevity. -- Genetic aspects; Aging